The impact of customer perceived service quality on customer satisfaction for private health centre in Malaysia: a structural equation modeling approach - Haque, A. K. M. Ahasanul; Sarwar, Abdullah Al-Mamun; Yasmin, Farzana; Anwar, Aftab; ., Nuruzzaman (International Foundation for Research and Development, 2012)
The main purpose of this paper is to develop and test the modified SERVQUAL model to measure Malaysian private healthcare quality. A total of 131 participants were selected randomly those visit private hospitals in Malaysia for healthcare facility. Then data were examined using means, correlations, principal component and exploratory factor analysis to establish the modified SERVQUAL scale’s reliability, underlying dimensionality and convergent, discriminant validity. This paper than utilizes the structural equation modeling technique to do confirmatory factor analysis and test the hypothesized positive inter-relationships between customer’s perception and customer satisfaction. This paper reviews and identifies essential service quality variables that are associated with the customer satisfaction in the private hospital. Customer satisfaction should reflect the need of healthcare quality requested by the customers, as direct and indirect relationships exist between personnel support and customer satisfaction and attention to customers and hospital facilities and between hospital facilities and customer satisfaction. The proposed model has been tested on only one private hospital in Malaysia due to short period. Due to this small sample size and the convenient method of data collection, there is a possibility of biasness of the authors may play a role in the outcome of the study. The main contribution of this study is that, it proposes a way to assess quality services in the private hospitals. This study has proposed a conceptual model that need further investigation and opens a way for future research.